Paper: Voice over Internet Protocol & Its Business & Growth Trends in Indian Market (International Journal of Emerging Trends in Science and Technology, 2017)
Voice over Internet protocol (VoIP), there is an existing way of communication over any network. The Userscan make the telephone calls over an IP network using this technology. This paper will describe Voice overInternet Protocol (VoIP) to a level that allows discussion of security issues and concerns. There are two kindsof spoofing attacks are possible, first one is IP spoofing attack and another is URI spoofing attack, which aredescribed in this review paper. The Implementation of VoIP concerned by businesses, components of a VoIPsystem, and relevant security issues. The business concerns will be those which are used to affect the Qualityof Service (QoS). The network components call processors, gateways and two of the more commonarchitectures are held by VoIP.